The Influence of Leadership, Competence and Work Environment on Performance of Health Office Employees in Indonesia - Wistri Vanumbari Lastianum; Izaak Zoelkarnain; Bahrul Ilmi; Syamsul Arifin; Rosihan Adhani (Jurnal Berkala Kesehatan, 2025)
In 2022, the evaluation of the Family Intervention Program in Indonesia’s public health sector showed a realization rate of 45.14% of the 50% target. This highlights the need to strengthen human resources to improve program performance. This meta-analysis examined the effects of leadership, competence, and work environment on the performance of health service employees in Indonesia. A total of 1,798 studies were identified, and 13 met inclusion criteria using the PRISMA method and were appraised with the JBI instrument. Data were analyzed using JASP 0.17.2.1 to estimate effect sizes via forest and funnel plots. Results indicated that leadership (p < 0.001; ES = 0.195), competence (p < 0.001; ES = 0.223), and work environment (p = 0.008; ES = 0.228) each significantly affected employee performance. The work environment had the largest overall influence. Strengthening these factors is essential to enhance the performance of Indonesia’s health workforce.